Downstream Targets of Cyclic Nucleotides in Plants - Świeżawska, Brygida; Duszyn, Maria; Jaworski, Krzysztof; Szmidt-Jaworska, Adriana (Frontiers in Plant Science, 2018)
Efficient integration of various external and internal signals is required to maintain adaptive cellular functioning. Numerous distinct signal transduction systems have evolved to allow cells to receive these inputs, to translate their codes and, subsequently, to expand and integrate their meanings. Two of these, cyclic AMP and cyclic GMP, together referred to as the cyclic nucleotide signalling system, are between them. The cyclic nucleotides regulate a vast number of processes in almost all living organisms. Once synthesized by adenylyl or guanylyl cyclases, transduce signal by acting through a number of cellular effectors. Because the activities of several of these effectors can be altered simultaneously in response to temporal changes in cyclic nucleotide level, cAMP/cGMP-elevating agents can trigger multiple signalling events that markedly affect the numerous cellular functions. In this mini review, we summarize how recent evidence supports the existence of cNMP effectors in plant cells. Specifically, we highlight cAMP-dependent protein kinase A (PKA), cGMP-dependent kinase G (PKG), cyclic nucleotide phosphodiesterases (PDEs). Essentially this manuscript documents the progress that has been achieved in recent decades in our understanding of the regulation and function of cNMPs in plants and on the other hand, emphasizes the current gaps and unanswered guestions in this field of plant signalling research.